Memoria plural Entrevistas a escritores latinoamericanos - TORRES FIERRO, Danubio (SUDAMERICANA, 1986)
CONTENIDO : BIANCO, JOSE; BIOY CASARES, ADOLFO; CABRAL DE MELO NETO, JOAO; CABRERA INFANTE, GUILLERMO; CAMPOS, HAROLDO DE; EDWARDS, JORGE; ELIZONDO, SALVADOR; FUENTES, CARLOS; GIRRI, ALBERTO; MOLINA, ENRIQUE; OROZCO, OLGA; PUIG, MANUEL; SABATO, ERNESTO; SARDUY, SEVERO; VARGAS LLOSA, MARIO